(untitled) (The Spectrum, 2025)
This article explores the dominant trends and debates surrounding the framing and conceptualization of disasters in scholarly discourse. While providing a global overview of various disasters, it focuses on how academic disciplines have defined and debated catastrophic events. The study examines how disasters are contested and the paradigms that shape this field. It follows a structured approach, beginning with a review of representative definitions of disaster, followed by an analysis of discourse on major international disasters, and concluding with an examination of prevalent paradigms. Additionally, it considers how disasters are mediated through myths and literary works. As a qualitative conceptual attempt, it draws insights, discussions, analyses, and inferences from secondary sources, including books, journals, and other written materials. The findings indicate while diverse disciplinary discussions have enriched the understanding of disaster scholarship. It concludes that, since disasters are interconnected events and processes rather than isolated incidents, they require a more holistic and comprehensive understanding.